PERANCANGAN MUTU COOKIES LIDAH KUCING UBI JALAR MENGGUNAKAN METODE QFD - Dini Nastiti Anjarsari; Bambang Herry Purnomo; Nurhayati Nurhayati (JURNAL AGROTEKNOLOGI, 2017)
UD. Nula Abadi is one of home industry that produces flour and the processed products from sweet potatoes in Bondowoso regency. Lidah kucing is one of UD. Nula Abadi cookies that has potential prospect to develop because these cookies can go into all of marketing segmentation. The aimed of this research are to identify costumer’s quality attribute and to design the quality of lidah kucing UD. Nula Abadi to fulfil costumer’s quality attribute. This research used quality function deployment. The result of this research shows that quality attribute which has being customers priority based on mapping with the technical requirements and competitive profile are taste, packaging material, and texture. The quality design that can be applied for UD. Nula Abadi are keeping the quality of sweet potato, calibrating scale machine, using oven that complete with timer and thermostat, using the packaging material that can be kept the shape of lidah kucing, training the employee to keep production process in accordance with standard operational procedure, having a partnership with local government in terms of promotion and business development. Keywords: sweet potatoes, cookies, QFD